Inequality: What Сan be Done? (an excerpt) - AtkinsonAnthony B. (Journal of Economic Sociology, 2017)
In this book addressing how best to reduce contemporary large-scale income inequality, Prof. Atkinson considers economic inequality from a new perspective, drawing on extensive historical data covering more than a century of evolution in modern societies. In the first of the book’s three parts, the author explains his research motivation and poses the following questions. What does inequality mean? To what extent is it expanding today? Has history ever witnessed periods of declining inequality? How can economic theory explain inequality? The second part of the book is devoted to specific political and economic policies designed to reduce inequality. In the third part, the author assesses the extent to which the policies he proposes can be considered realistic, discussing the pros and cons of enacting and implementing them. The Journal of Economic Sociology publishes the first chapter “Setting the Scene,” which puts readers in the picture by discussing the notion of inequality and its extent. Demonstrating the term’s multiplicity of meanings, Atkinson argues that all questions concerning its main dimensions should be answered before searching for its foundations.